Thyroid function analysis after roxadustat or erythropoietin treatment in patients with renal anemia: a cohort study - Xiaomeng Zheng; Yiyi Jin; Tao Xu; Hongbin Xu; Suyan Zhu (Renal Failure, 2023)
Purpose This cohort study was designed to explore whether roxadustat or erythropoietin could affect thyroid function in patients with renal anemia.Methods The study involved 110 patients with renal anemia. Thyroid profile and baseline investigations were carried out for each patient. The patients were divided into two groups: 60 patients taking erythropoietin served as the control group (rHuEPO group) and 50 patients using roxadustat served as the experimental group (roxadustat group).Results The results indicated that there were no significant differences in serum total thyroxine (TT4), total triiodothyronine (TT3), free triiodothyronine (FT3), free thyroxine (FT4) or thyroid stimulating hormone (TSH) between the two groups at baseline. After treatment, TSH, FT3, and FT4 were significantly lower in the roxadustat group than in the rHuEPO group (p < 0.05). After adjusting for age, sex, dialysis modality, thyroid nodules and causes of kidney disease, Cox regression showed that roxadustat was an independent influencing factor on thyroid dysfunction (HR 3.37; 95% CI 1.94–5.87; p < 0.001). After 12 months of follow-up, the incidence of thyroid dysfunction was higher in the roxadustat group than in the rHuEPO group (log-rank p < 0.001).Conclusion Roxadustat may lead to a higher risk of thyroid dysfunction, including low TSH, FT3 and FT4, than rHuEPO in patients with renal anemia.